Malnutrition and Obesity Prevalences in Geriatric Patients: Malnutrition and Obesity Prevalences - Turkbeyler, İbrahim H and Ozturk, Zeynel A and Abiyev, Azer and Efendioglu, Eyüp M and Yildiz, Hamit (Progress in Nutrition, 2020)
Aim: All societies, including Turkish society, are experiencing a dramatic growth in proportion of elderly individuals. Geriatric malnutrition and obesity are substantial health problems. The aim of this study is to investigate the prevalence of malnutrition and obesity in elderly individuals who attended a geriatric outpatient clinic in Turkey. Methods: This study included 520 elderly patients. All patients underwent Mini Nutritional Assessment–Short Form (MNA-SF) test via face to face interview. The participants were divided into four groups, as follows: underweight group (BMI<20.0 kg/m2), normal weight group (BMI 20.0–24,9 kg/m2), overweight group (BMI 25.0–29,9 kg/m2) and obese group (BMI≥30 kg/m2). Results: The mean age was 71.8±5.8 and 285 patients (54.8%) were female. 11 (2.1%) of the patients were underweight, 91 (17.5%) were normal, 193 (37,1%) were overweight and 225 (43.3%) were obese. According to MNA-SF, 37 (7.1%) were diagnosed with malnutrition, 165 (31.7%) were at risk of malnutrition, and 318 (61.2%) displayed a good nutritional status. 43.3% of the whole were obese. 68.7% of them were obese or diagnosed with malnutrition or at risk of malnutrition. 33.7% were obese and either diagnosed with malnutrition or at the risk of malnutrition. 38.8% were either at risk of malnutrition or diagnosed with malnutrition. Discussion: Two of every three elderly patients exhibited malnutrition or risk of malnutrition or obesity. To prevent malnutriton and obesity in old age, elderly patients should be evaluated comprehensively through several domains including medical, nutritional, or social status and certain novel strategies should be devised to promote physical activity and to raise awareness about the nutrition throughout the society.